On cell range extension in LTE‐Advanced Type 1 inband relay networks. Issue 4 (11th June 2013) - Saleh, Abdallah Bou; Bulakci, Ömer; Redana, Simone; Hämäläinen, Jyri
ABSTRACT Relay node cell area is limited by low transmission power and limited antenna capabilities, which may not allow it to carry a significant share of the traffic load, thus reducing its efficiency. Cell range extension is thus expected to better balance the load in the network, hence, improving the performance of relay deployments. Herein, we investigate two relay cell range extension techniques, introducing a bias to cell selection and handover thresholds along with reduction in donor enhanced Node B transmission power. The study focuses on inband half‐duplex relaying where resource partitioning among the two relay hops is jointly considered with cell range extension. As opposed to picocell deployments, extending the relay cell range offloads only partially the macrocell as newly admitted users increase the resource demand of the relay on its wireless backhaul link from its donor enhanced Node B. Hence, joint optimization of the decisive parameters for different key performance metrics is performed. Comprehensive analysis was carried out for both the downlink and the uplink in urban and suburban scenarios within the LTE‐ Advanced framework. Results reveal that the investigated solution yields significant gains. Finally, we discuss on the realization of cell range extension as part of network planning and offline optimization.Copyright © 2013 John Wiley & Sons, Ltd.